2011
DOI: 10.1007/s10803-011-1260-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Imbalance Associated with Methylation Dysregulation and Oxidative Damage in Children with Autism

Abstract: Oxidative stress and abnormal DNA methylation have been implicated in the pathophysiology of autism. We investigated the dynamics of an integrated metabolic pathway essential for cellular antioxidant and methylation capacity in 68 children with autism, 54 age-matched control children and 40 unaffected siblings. The metabolic profile of unaffected siblings differed significantly from case siblings but not from controls. Oxidative protein/DNA damage and DNA hypomethylation (epigenetic alteration) were found in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
214
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(236 citation statements)
references
References 81 publications
14
214
3
3
Order By: Relevance
“…Research studies have shown that insufficient dietary folate increases requirement for choline and betaine-derived methyl groups and conversely, choline and betaine deficiency increases the requirement for folate-derived methyl groups [17]. Thus, dietary deficits in both pathways for methionine synthesis may be compromised in children with ASDs and additively contribute to the low methionine and SAM levels previously reported in these children [8][9][10]. Importantly, reduced synthesis of SAM, the major intracellular methyl donor, can lead to DNA hypomethylation and epigenetic abnormalities associated with abnormal gene expression, genomic imprinting, and genomic instability [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research studies have shown that insufficient dietary folate increases requirement for choline and betaine-derived methyl groups and conversely, choline and betaine deficiency increases the requirement for folate-derived methyl groups [17]. Thus, dietary deficits in both pathways for methionine synthesis may be compromised in children with ASDs and additively contribute to the low methionine and SAM levels previously reported in these children [8][9][10]. Importantly, reduced synthesis of SAM, the major intracellular methyl donor, can lead to DNA hypomethylation and epigenetic abnormalities associated with abnormal gene expression, genomic imprinting, and genomic instability [22].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, reduced synthesis of SAM, the major intracellular methyl donor, can lead to DNA hypomethylation and epigenetic abnormalities associated with abnormal gene expression, genomic imprinting, and genomic instability [22]. Significant decreases in plasma methioinine and SAM associated with DNA hypomethylation have been reported in children with ASDs relative to age-matched control children [10]. It is not known whether supplemental choline or betaine would increase methionine and SAM synthesis in children with autism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant overrepresentation of genes with functions in chromatin regulation and early developmental expression was found in ASD probands but not in unaffected siblings [106]. Also, oxidative protein/DNA damage and DNA hypomethylation (epigenetic alteration) were found in autistic children but not paired siblings or controls [107]. So, nowadays attention has turned to environmental factors but also with epigenetic changes as potential etiological agents predisposing to autism susceptibility.…”
Section: Epigenetic Changes Involved In Asdmentioning
confidence: 99%
“…Low plasma SAM levels and DNA hypomethylation have been shown to be present in children with autism [107]. Choline deficiency has been also shown in animal models to contribute to global and gene-specific DNA hypomethylation and epigenetic abnormalities [317].…”
Section: Vitamin-like Substances: Cholinementioning
confidence: 99%